HOW TO TEACH VOCABULARY IN ENGLISH LANGUAGE - Vallamatova, S. S.; Munavvarova, N. I. (INTERNATIONAL CONFERENCES, 2023)
The article reflects on effective methods and stages of teaching vocabulary and some information about vocabulary, word, meaning and their types are given and discussed.